Management of severe hyperinflammation in the COVID-19 era: the role of the rheumatologist. (16th November 2020) - Papadopoulou, Charalampia; Al Obaidi, Muthana; Moraitis, Elena; Compeyrot-Lacassagne, Sandrine; Eleftheriou, Despina; Brogan, Paul
Abstract: Objectives: The objectives of this study were (i) to describe the clinical presentation, treatment and outcome of paediatric inflammatory multisystem syndrome temporally related to Sars-CoV-2 (PIMS-TS) in children; (ii) to propose a framework to guide multidisciplinary team (MDT) management; and (iii) to highlight the role of the paediatric rheumatologist in this context. Methods: This study involved a retrospective case notes review of patients referred to a single specialist paediatric centre with suspected PIMS-TS, with a focus on clinical presentation, laboratory parameters, treatment, and outcome in the context of an MDT framework. Results: Nineteen children of median age 9.1 years fulfilled the definition of PIMS-TS and were managed within an MDT framework: 5/19 were female; 14/19 were of Black, Asian or minority ethnicity; 9/19 also fulfilled diagnostic criteria for complete or incomplete Kawasaki disease (KD). Severe systemic inflammation, shock, and abdominal pain were ubiquitous. Treatment was stratified within an MDT framework and included CSs in all; i.v. immunoglobulin in all; anakinra in 4/19; infliximab in 1/19; and antiviral (aciclovir) in 4/19. Conclusions: We observed significant diagnostic equipoise using a current definition of PIMS-TS, overlapping with KD. Outside of clinical trials, an MDT approach is vital. The role of the paediatric rheumatologist is to consider differential diagnoses of hyperinflammation in the young, to advise on empiric immunomodulatory therapy, to set realistic therapeutic targets, to gauge therapeutic success, to oversee timely step-down of immunomodulation, and to contribute to the longer-term MDT follow-up of any late inflammatory sequelae.